A longitudinal study of hormonal and semen profiles in a marathon runners - Jensen, Carl Edward (Department of Obstetrics and Gynaecology, 2018)
Over the past decade long distance marathon running has become an important recreational activity. There is evidence that males with high levels of physical activity have some impairment of fertility. In order to investigate this further, 24 male marathon runners were studied over a period of a year. Each runner was assessed at regular intervals using hormonal profiles, anthropomorphic indices and semen evaluation. The training time and distance run increased progressively over the first five months of the study as the runners prepared for the Two Oceans marathon. Analysis of the serum hormonal profiles in this longitudinal study showed that the prolactin level increased when comparing the initial study month with the rest of the year and the progesterone level decreased. However the luteinizing hormone (LH), follicle stimulating hormone (FSH), testosterone and estradiol (E2) levels remained unchanged. When the runners were divided into a high and low training group according to the distance run in the preceding week, the only significant difference was the lower mean serum FSH level in the high training group. A decrease in semen volume was demonstrated as the training time increased. This trend was reversed as the runners' training decreased after the Two Oceans marathon. The percentage of morphologically normal spermatozoa showed an initial significant decrease in the first month of training. However, no significant difference was observed throughout the rest of year. An overall downward trend in semen motility in the first 5 months of the study was shown but this was only significant if the first and fifth study months were compared. The decrease in semen motility coincided with the period of maximum training. Since patients with an adequate sperm count but decreased motility have impaired fertility this finding is of considerable importance. In addition to the decrease in motility, there was a decrease in the percentage of morphologically normal spermatozoa when the initial month of low physical activity (December) was compared to all of the subsequent months analysed. This, too, is an important finding as the percentage of morphologically normal spermatozoa correlates directly with fertilisation and pregnancy rates. When the results were analysed in the high and low training months there was a significant difference in mean semen count and semen morphology. The mean count was higher in the high training group and this group also had a significantly higher normal morphology. However, there was no significant difference in semen volume and motility in the high and low training groups.